2018
DOI: 10.1590/2177-9465-ean-2017-0404
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces of violence with and nursing education: a possible and necessary dialogue

Abstract: Objective: To identify the professors' ideals and practices of undergraduate nursing education regarding the presence of violence during the teaching-learning process. Methods: Qualitative, descriptive and exploratory research, performed by 19 professors.For the collection of the information it had been used the Creativity and Sensitivity Dynamics. The data had been analyzed establishing its approximation with the referential present in Paulo Freire's works. Results: Violence is, on the theoretical and practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Study by Zanatta et al (2018), conducted with 19 nursing graduate educators from two Higher Education Institutions (HEIs) in Santa Catarina (Brazil), revealed that the theme violence is worked in an elementary way, with superficial critical reflection on the practice, reflecting the invisibility of the approach of the theme in the pedagogical projects of the course (PPCs). Thus, nurses have insufficient preparation for the care of victims of violence (Martins et al, 2017).…”
mentioning
confidence: 99%
“…Study by Zanatta et al (2018), conducted with 19 nursing graduate educators from two Higher Education Institutions (HEIs) in Santa Catarina (Brazil), revealed that the theme violence is worked in an elementary way, with superficial critical reflection on the practice, reflecting the invisibility of the approach of the theme in the pedagogical projects of the course (PPCs). Thus, nurses have insufficient preparation for the care of victims of violence (Martins et al, 2017).…”
mentioning
confidence: 99%